The Development of the Consumer Brand Engagement Scale Through Social Media Advertising - Supotthamjaree, Weeraporn; Srinaruewan, Preeda (NIDA Business Journal, 2022)
The concept of Consumer Brand Engagement (CBE) is an issue attracting attention from marketing scholars in recent years since it is a scale of brand performance through social media advertising. However, as previous studies used different concepts, definitions, and dimensions of CBE, this study has adopted the research of Hollebeek et al. (2014) as a guideline to develop a CBE scale and to extend the previous knowledge in the Confirmatory Factor Analysis (CFA) by analyzing CBE as the second-order confirmatory factor after the first-order confirmatory factor comprising of cognitive, emotional, and behavioral factors. The results of the second-order confirmatory factor analysis from 560 samples can confirm that CBE factors are a structure consisting of three dimensions: cognitive, emotional, and behavioral dimensions. Moreover, the analysis of results shows a high level of convergent validity, discriminant validity, and construct reliability. This study is an extension of previous knowledge, analysis of CBE; which is the second-order confirmatory factor reflecting three dimensions: cognitive, emotional, and behavioral dimensions. In addition, entrepreneurs may apply the findings as a measurement of CBE through social media advertising.